PP.41 Management of Obesity in Pregnancy in the West of Scotland. (26th April 2013) - Wu, P; McMillan, M; Moss, H; Gibson, JL
Abstract : In 2012, a prospective 3-month audit of management of obesity in pregnancy was undertaken in Glasgow and Clyde maternity hospitals comparing practise to CMACE/RCOG guideline. 1 214 women were identified out of 3, 834 deliveries: 138 (64%) had a booking body mass index (BMI) of 35–39 whilst 76 (36%) had a BMI ≥ 40. Out of total deliveries, 3.5% had a BMI of 35–39 and 2.0% had a BMI ≥40. 43 (31%) women took folic acid preconception which increased to 125 (91%) women in first trimester. However, only 2 women took 5 mg preconception and 7 took this during first trimester. Only 4 women had documented evidence of vitamin D supplementation. Hand-held records were available in 197 cases and 193 (98%) women had booking BMI recorded. Anaesthetic review occurred in 68 (89%) women with BMI ≥ 40. Antenatal thromboprophylaxis was indicated in 43 women, but 11 women received it. Postnatally, all women with BMI ≥ 40 should have thromboprophylaxis, however 50 (66%) received this, out of which 14 women received appropriate dose for weight. Though only 21 (10%) women had glucose tolerance test in BMI 35–39 group, this increased to 44 (58%) women in BMI ≥ 40 group. 44 (58%) women with BMI ≥ 40 had obstetric staff of specialty trainee year ≥6 in attendance at delivery. There is good compliance of guideline with 195 (91%) women having documented active management of third stage and only 1 woman induced for BMI. We conclude that some CMACE/RCOG recommendations have been implemented, though there is much scope for improvement. Reference: Centre for Maternal and Child Enquires/Royal College of Obstetricians and Gynaecologists Joint Guideline. Management of women with obesity in pregnancy. March 2010.